Effect of Perceived Stress on Cytokine Production in Healthy College Students. (April 2015) - Sribanditmongkol, Vorachai; Neal, Jeremy L.; Patrick, Thelma E.; Szalacha, Laura A.; McCarthy, Donna O.
Chronic psychological stress impairs antibody synthesis following influenza vaccination. Chronic stress also increases circulating levels of proinflammatory cytokines and glucocorticoids in elders and caregivers, which can impair antibody synthesis. The purpose of this study was to determine whether psychological stress increases ex vivo cytokine production or decreases glucocorticoid sensitivity (GCS) of peripheral blood leukocytes from healthy college students. A convenience sample of Reserve Officer Training Corps (ROTC) students completed the Perceived Stress Scale (PSS). Whole blood was incubated in the presence of influenza vaccine and dexamethasone to evaluate production of interleukin-6 (IL-6), interleukin-1-beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and interferon-gamma (IFN-γ). Multiple regression models controlling for age, gender, and grade point average revealed a negative relationship between PSS and GCS for vaccine-stimulated production of IL-1β, IL-6, and TNF-α. These data increase our understanding of the complex relationship between chronic stress and immune function.